1997
DOI: 10.1172/jci119644
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic gluconeogenic fluxes and glycogen turnover during fasting in humans. A stable isotope study.

Abstract: Fluxes through intrahepatic glucose-producing metabolic pathways were measured in normal humans during overnight or prolonged (60 h) fasting. The glucuronate probe was used to measure the turnover and sources of hepatic UDP-glucose; mass isotopomer distribution analysis from

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
176
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 175 publications
(195 citation statements)
references
References 40 publications
17
176
2
Order By: Relevance
“…However, this release occurred after infusion over 10 h of approximately 3·5 g galactose, 2·2 g glucose, 9 g glycerol, 21 g propylene glycol (equivalent to 25 g lactic acid) and 4 g ethanol, so their subjects were questionably in the fasting state. Hellerstein et al (1997) also conclude that glycogen cycling occurred because after the 10 h of infusion the contribution of GNG calculated by MIDA was 84-96 %, compared with the 78 % after 4 h of infusion. They imply this means replacement over time of the unlabelled glucosyl units of glycogen by labelled units formed via GNG, i.e.…”
Section: Mass-isotopomer-distribution Analysismentioning
confidence: 68%
See 3 more Smart Citations
“…However, this release occurred after infusion over 10 h of approximately 3·5 g galactose, 2·2 g glucose, 9 g glycerol, 21 g propylene glycol (equivalent to 25 g lactic acid) and 4 g ethanol, so their subjects were questionably in the fasting state. Hellerstein et al (1997) also conclude that glycogen cycling occurred because after the 10 h of infusion the contribution of GNG calculated by MIDA was 84-96 %, compared with the 78 % after 4 h of infusion. They imply this means replacement over time of the unlabelled glucosyl units of glycogen by labelled units formed via GNG, i.e.…”
Section: Mass-isotopomer-distribution Analysismentioning
confidence: 68%
“…In accordance with the absence of a single precursor pool, when [U-13 C 3 ]glycerol was infused for 5 h into healthy subjects fasted for 60 h the contribution of GNG to glucose production was estimated to be only 60 % (Landau et al 1995b), and only 78 % when infused with [2-13 C]glycerol for 4 h (Hellerstein et al 1997), rather than > 90 % expected with glycogen depletion. The greater percentage contribution with [2-13 C]glycerol when compared with [U-13 C 3 ]glycerol can be explained by the need to infuse more [2-13 C]glycerol, resulting in a smaller concentration gradient along the liver lobule.…”
Section: Mass-isotopomer-distribution Analysismentioning
confidence: 79%
See 2 more Smart Citations
“…A recent study has estimated that glycogenolysis contributes about 60% of the hepatic glucose production in overnight fasted type 2 diabetes patients [7]. Furthermore, it has been reported that a substantial portion of gluconeogenesis appears to be cycled through the glycogen pool prior to efflux from the liver [8], and that glycogen phosphorylase inhibitors indirectly inhibit gluconeogenesis by disrupting the glucose/glycogen cycling involved in hepatic glucose production [9]. Thus, inhibition of glycogenolysis by glycogen phosphorylase inhibitor may prove beneficial in the treatment of type 2 diabetes.…”
Section: Discussionmentioning
confidence: 99%